Achalasia Associated with Neurofibromatosis - Stephen N Sullivan (Canadian Journal of Gastroenterology)
A 32-year-old patient with neurofibromatosis who developed achalasia is reported. At the second pneumatic dilation the esophagus was perforated, requiring surgical repair and myotomy. The patient made an uneventful recovery and now swallows without difficulty. This is the second report of this association.